Patient perspectives of the influence of severe and non‐severe asthma on their quality of life: A national survey of asthma patients in Spain. (17th November 2021) - Chiner, Eusebi; Hernández, Carme; Blanco‐Aparicio, Marina; Funenga‐Fitas, Eunice; Jiménez‐Ruiz, Carlos
Abstract: Introduction: Little is known about adult asthma patients' perspective of their disease burden. This study aimed to obtain a comprehensive picture of patient needs, evaluate their knowledge, source of information, and perception of the severity of their asthma, and compare these variables between severe (SA) and non‐severe (NSA) asthma patients. Methods: We conducted an online cross‐sectional survey in Spain among asthma patients aged ≥18 years. A bespoke questionnaire was used to collect sociodemographic data, asthma characteristics, treatments, disease burden, patient's perception of disease severity, and asthma information sources. Patients were classified as SA and NSA according to GINA 2020 treatment steps recommendations. To compare populations, 600 participants (200 SA and 400 NSA) were randomly selected to complete the survey. Results: Participants were mostly women, mean age >38 years. SA patients underestimated the severity of their asthma; 52% judged it as mild, and only 2% considered their asthma severe. Overall, 50% of NSA and 96% of SA patients had experienced ≥1 exacerbation the previous year ( p < 0.001). Fewer asthma exacerbations (SA) and improved quality of life (QoL) (NSA) were the most frequently expected therapy outcomes. NSA patients believe that asthma impacts their daily life (37%) and worsens QoL (34%) to a lesser degree than SA (67% and 59%, respectively; p < 0.001). Patient‐preferred sources of information were specialists (NSA:42%; SA: 38%) and primary care physicians (NSA: 41%; SA: 33%). Conclusions: Despite the effective therapies currently available, the results of this study still show a significant emotional burden and QoL impairment in patients with severe asthma.